Why do some consumers shop in this pharmacy? A cross-check of vulnerable characteristics and store types. (May 2016) - Meng, Jie; Layton, Roger; Huang, Yimin
Abstract: Research on vulnerable consumers remains unfailing in macromarketing and social marketing. Yet it is unclear how to operationalize the vulnerable consumers by demographics and further to this it is rarely touched how the vulnerable consumers defined by different measures make decision when choosing the place to shop especially in pharmacy retailing sector. The authors conduct a comparative study of variously-defined vulnerable consumers for their shopping store types in an urban Chinese city to investigate how people with distinct backgrounds develop their decision making rules and choose different types of retail pharmacies. This paper casts light on customer heterogeneity associated with different dimensions of vulnerability by using consumer demographics, and indicates that four dimensions of vulnerability exist as cognitive capability, social relations, behaviors, and the institutional protection in health-related sector. These four aspects of vulnerability play a significant role in identifying different shop selection patterns. Findings suggest that efforts to boost store patronage targeting on various consumer groups should have different strategies to reach consumers' mindsets. Highlights: It's important to operationalize demographical variables to segment the vulnerable consumers and practical measures of consumer decisions in shop choices. This study presents a comparative study to investigate how people with distinct backgrounds develop their decision making rules and choose different retail types. Findings show customer heterogeneity associated with different dimensions of vulnerability and indicate four dimensions of vulnerability e.g. cognitive capability, social relations, behaviors, and the institutional protection. These four aspects of vulnerability play a significant role in identifying different shop selection patterns and improving customer patronage.